AL-‘ASHER SCHOOL: THE PHILOSOPHICAL OF K.H. AHMAD DAHLAN’S CHARACTER EDUCATION - Khoirudin, Azaki; Anshori, Ari (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2018)
This article is a philosophical reflection of KH. Ahmad Dahlan educational practice. Based on the historical fact that KH. Ahmad Dahlan undertook the character education contained in Surah Al-'Ashr to his students for 7-9 months. This educational practice is manifested in the form of ?Pengajian Wal-'Ashri? for young women and ?Wal-'Ashri Cadre School? for male youth. This makes the spirit and ethos of al-'Ashr embedded in young men and women, thus creating a "theology of pious charity" (amal shaleh). The theology encourages the spirit of praxis and activism of Muhammadiyah followers to perform humanitarian work in the fields of education, health, social, economics, community empowerment, philanthropy and others later known as " al-Ma'un theology" and "Al-?Ashr theology ". Using the perspective of the philosophy of reconstructionist education of George Count and Bourdieu's sociology approach to social practice, it can be concluded that Muhammadiyah education gave birth to a religious-transformative character inspired by Surah Al-'Ashr.